2016
DOI: 10.1371/journal.pone.0154367
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Bone Morphological and Trabecular Bone Microarchitectural Changes in the Mandible and Femoral Neck of Ovariectomized Rats

Abstract: ObjectiveThis study used microcomputed tomography (micro-CT) to evaluate the effects of ovariectomy on the trabecular bone microarchitecture and cortical bone morphology in the femoral neck and mandible of female rats.Materials and MethodsTwelve female Wister rats were divided into two groups: the control and ovariectomized groups. The rats in the ovariectomized group received ovariectomy at 8 weeks of age; all the rats were sacrificed at 20 weeks of age, and their mandibles and femurs were removed and scanned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
43
0
10

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(58 citation statements)
references
References 57 publications
(75 reference statements)
5
43
0
10
Order By: Relevance
“…The thickness in the OVX group were significantly lower than those found in the SHAM group, and the trabecular separation was 4-fold higher in the OVX group than in the sham group. With a more approximated experimental design of this work, Hsu et al 28 found results similar to this work, by microcomputed tomography, but in other regions that are mandible and femoral neck.…”
supporting
confidence: 70%
“…The thickness in the OVX group were significantly lower than those found in the SHAM group, and the trabecular separation was 4-fold higher in the OVX group than in the sham group. With a more approximated experimental design of this work, Hsu et al 28 found results similar to this work, by microcomputed tomography, but in other regions that are mandible and femoral neck.…”
supporting
confidence: 70%
“…The Percent Bone Volume parameter determines the ratio of bone volume within the Volume-of-Interest Object that is used to measure bone mass related to non-mineralized tissue of the sample (Cesar et al 2013, Hsu et al 2016, Longo et al 2017. In this study, the percentage in group G3 and G4 were higher for both trabecular bone and cortical bone compared to group G1 and G2.…”
Section: Discussionmentioning
confidence: 83%
“…For a general analysis of the cortical and trabecular bone, the following parameters were considered: Tissue Volume, Bone Volume, and Percent Bone Volume, especially when assessing the relationship between the bone matrix and other tissues. Tissue Volume was essentially based on bone structure since tíbia samples were dissected (Buie et al 2007, Larriera et al 2011, Hsu et al 2016, which was different from other studies performing in vivo analysis (Link et al 1999, Wehrli et al 2003, Buie et al 2007). The result for Bone Tissue Volume was similar to Bone Volume.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations